Urban Green Renaissance in Malang: Trunojoyo Park and the Path to Sustainable Urban Futures - Laraswati, Nadia Trikarlina; Basri, Igo Maulana; Sogen, Rafael Miku P.; Angelina, Cut Puan Galuh; Poerwati, Titik; Desderius, Kevie (Badan Perencanaan Pembangunan Kota Malang, 2026)
Urban green spaces play a crucial role in promoting ecological resilience, social inclusion, and sustainable city development. This study examines Trunojoyo Park in Malang as a representative case of mid-sized Indonesian urban parks, analyzing its ecological functions, infrastructure conditions, accessibility features, and patterns of visitor utilization. The research applies a descriptive qualitative approach using a case study design, supported by field observation, document review, and spatial analysis. The analytical approach employs interactive analysis techniques consisting of data reduction, data display, and conclusion drawing, combined with spatial interpretation to assess ecological and functional performance of the park. Findings reveal that the park provides important ecosystem services, including air quality improvement, carbon sequestration, stormwater regulation, and urban heat island mitigation. It also accommodates diverse recreational, cultural, and educational activities, serving as a vital community hub. However, several limitations remain evident, such as deteriorating infrastructure, inadequate drainage systems, limited vegetation diversity, and insufficient universal accessibility. These issues restrict the park’s overall performance and reduce inclusivity for vulnerable groups. The discussion highlights the urgency of revitalizing Trunojoyo Park to enhance ecological design, strengthen accessibility, and modernize management systems through smart technologies and participatory governance. By addressing these priorities, Trunojoyo Park can evolve into a resilient and inclusive green space that not only supports environmental services but also fosters social equity and cultural vitality. This case study underscores the importance of integrating ecological principles and community-centered approaches in urban park planning to advance sustainable urban futures.